Surface plasmon resonance sensors : a materials guide to design and optimization /: a materials guide to design and optimization. ([2015]) - Oliveira, Leiva Casemiro; Lima, Antonio Marcus Nogueira; Thirstrup, Carsten; Neff, Helmut Franz
No abstract available